Non-addictive Information Systems - Simon Kloker (Information Systems Frontiers, 2020)
Addiction in the context of information technology gained increased public interest within the last years. Only recently, companies like Apple, Google, and Instagram announced to fight smartphone addiction and integrated matching features in their systems. However, if and how these features really help is still an open question. At present, there is only a very rudimentary understanding of IT-triggered disorders and addictions in information systems. Even in clinical research, there is no consensus on the nature of these addictions yet. Nevertheless, the omnipresence of information technology in our daily lives and its unpredictable effects on our moods require this problem~to be addressed in a profound manner. This paper links findings from psychology and neuroscience to the information systems terminology and derives the Four-Component Model for Non-addictive Information Systems (4-NAIS). The 4-NAIS allows locating how information technology interacts with the reinforcement cycle of addictions and provides a deeper understanding of where interventions and design decisions may really help tackle IT-triggered disorders.
Keywords: 000; Internet addiction; IT-triggered disorders; Non-addictive information systems; Framework development